Supernova [videorecording (DVD)] - Macqueen, Harry, 1984-; Firth, Colin, 1960-; Tucci, Stanley; Haywood, Pippa; Dreyfus, James (Wolfe Video, 2021)
A gay couple, one a musician, the other a novelist, embark on a road trip as dementia starts to take hold of one of them.